2014
DOI: 10.1007/s10682-014-9697-8
|View full text |Cite
|
Sign up to set email alerts
|

Sensory drive speciation and patterns of variation at selectively neutral genes

Abstract: Speciation by sensory drive can occur if divergent adaptation of sensory systems causes rapid evolution of mating traits and the resulting development of assortative mating. Previous theoretical studies have shown that sensory drive can cause rapid divergent adaptive evolution from one to two phenotypes. In this study, we examined two topics: the possibility of adaptive radiation by sensory drive from one to more than two phenotypes and the relationships of patterns of variation at selectively neutral genes to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…According to the theory of sensory-driven speciation, differences in important sensory traits can lead to assortative mating and reproductive isolation among populations (Fuller & Endler, 2018;Kawata et al, 2007;Matsumoto, Terai, Okada, & Tachida, 2014;Puechmaille et al, 2011). Under the hypothesis of sensory-driven speciation, genetic divergence is directly correlated with sensory divergence, which causes a pattern that we call "isolation by sensory variation" (IBS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the theory of sensory-driven speciation, differences in important sensory traits can lead to assortative mating and reproductive isolation among populations (Fuller & Endler, 2018;Kawata et al, 2007;Matsumoto, Terai, Okada, & Tachida, 2014;Puechmaille et al, 2011). Under the hypothesis of sensory-driven speciation, genetic divergence is directly correlated with sensory divergence, which causes a pattern that we call "isolation by sensory variation" (IBS).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing numbers of studies have provided empirical support for the importance of sensory drive in the speciation process (Boughman, 2002; Kawata, Shoji, Kawamura, & Seehausen, 2007; Puechmaille et al., 2011; Seehausen et al., 2008; Tobias et al., 2010). According to the theory of sensory‐driven speciation, differences in important sensory traits can lead to assortative mating and reproductive isolation among populations (Fuller & Endler, 2018; Kawata et al., 2007; Matsumoto, Terai, Okada, & Tachida, 2014; Puechmaille et al., 2011). Under the hypothesis of sensory‐driven speciation, genetic divergence is directly correlated with sensory divergence, which causes a pattern that we call “isolation by sensory variation” (IBS).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, earlier genetic studies suggested that there is no gene flow between P. h. himantegus and P. h. chii (Chang et al 2014;Chang et al 2009b), and therefore, it is possible that speciation by sensory drive promotes differentiation of these two bitterlings. Matsumoto et al (2014) suggested that speciation by sensory drive most likely occurs when the sensory trait is determined by a small number of loci. Indeed, the visual spectral sensitivity is related to the opsin genes, e.g., long-wavelength-sensitive opsin gene (lws) in cichlids, zebrafish (Danio rerio), and three-spined stickleback (Seehausen et al 2008;Shao et al 2014), or shortwavelength-sensitive opsin gene 2a (sws2a) in cichlids (Seehausen et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Terrestrial animals probe the environment for information about food, mates, and danger 1 , 2 by binding odor molecules to odorant receptors (ORs). Variation in mammalian ORs is linked to dietary niche, habitat, and sociability.…”
Section: Introductionmentioning
confidence: 99%